Force & motion - Twist, Clint (New York : Bearport Pub., 2006)
Presents a children's book for early readers that describes force and motion, and examines pushing, pulling, changes in motion, slopes, friction, changing shape and direction, and more.
Includes index.
Library Media Connection starred.
2.5
K-3
Keywords: Force and energy -- Juvenile literature; Motion -- Juvenile literature; Force and energy; Motion; Force and energy; Motion